Exploring the perception and socio-cultural barriers to safer sex negotiation among married women in Northwest Nigeria - Abayomi Folorunso Awoleye; Bola Lukman Solanke; Joseph Ayodeji Kupoluyi; Olufemi Mayowa Adetutu (BMC, 2022)
Abstract Background Safer sex negotiation refers to the means through which partners in sexual relationships agree to have intercourse that protects both partners from adverse sexual health outcomes. Evidence is sparse on the socio-cultural barriers to safer sex negotiation, especially in Northwest Nigeria where almost every aspect of women's lives is influenced by religious and cultural norms. Understanding the socio-cultural barriers requires having knowledge of the perspectives of community stakeholders such as religious leaders, and community leaders. Thus, from the perspectives of community stakeholders, this study explored the perception and socio-cultural barriers to safer sex negotiation of married women in Northwest Nigeria. Method A qualitative research design was adopted. Participants were purposively selected across six states, namely, Kano, Katsina, Jigawa, Kebbi, Kaduna, and Zamfara. Data were collected through Key Informant Interview (KII). A total of 24 KIIs were conducted using the in-depth interview guide developed for the study. The selection of the participants was stratified between rural and urban areas. The interviews were tape-recorded, transcribed, and translated from the Hausa language into the English language. Verbal and written informed consent were obtained from participants prior to the interviews. Data were analyzed using inductive thematic content analysis. Results Safer sex negotiation was well-understood by community stakeholders. Men dominate women in sexual relationships through the suppression of women's agency to negotiate safer sex. Married women endured domination by males in sexual relationships to sustain conjugal harmony. The practice of complying with traditional, cultural, and religious norms in marital relationships deters women from negotiating safer sex. Other socio-cultural causes of the inability to negotiate safer sex are child marriage, poverty, poor education, and polygyny. Conclusion Community stakeholders have a clear understanding of safer sex negotiation in Northwest Nigeria but this has not translated into a widespread practice of safer sex negotiation by married women due to diverse socio-cultural barriers. Strategies that will empower women not only to gain more access to relevant sexual and reproductive health information and services but also to encourage women's assertiveness in family reproductive health decisions are imperative in Northwest Nigeria.